2007
DOI: 10.1021/bi701213s
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β(1−42) Rapidly Forms Protofibrils and Oligomers by Distinct Pathways in Low Concentrations of Sodium Dodecylsulfate

Abstract: Alzheimer's disease (AD) is characterized by large numbers of senile plaques in the brain that consist of fibrillar aggregates of 40- and 42-residue amyloid-beta (Abeta) peptides. However, the degree of dementia in AD correlates better with the concentration of soluble Abeta species assayed biochemically than with histologically determined plaque counts, and several investigators now propose that soluble aggregates of Abeta are the neurotoxic agents that cause memory deficits and neuronal loss. These endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
179
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(202 citation statements)
references
References 75 publications
15
179
0
4
Order By: Relevance
“…Recently, a 12-16-mer oligomeric species of A␤42 called "globulomers" was reported to be formed independently of the fibril formation pathway (18), and a similar observation was reported for a 9 -15-mer species generated in the presence of SDS (19). Moreover, annular protofibrils (APFs) formed from prefibrillar oligomers (PFOs) failed to convert to fibrils even after an extended period of time, suggesting that these pathogenic oligomers are formed outside the nucleation-dependant fibril formation pathway (20).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Recently, a 12-16-mer oligomeric species of A␤42 called "globulomers" was reported to be formed independently of the fibril formation pathway (18), and a similar observation was reported for a 9 -15-mer species generated in the presence of SDS (19). Moreover, annular protofibrils (APFs) formed from prefibrillar oligomers (PFOs) failed to convert to fibrils even after an extended period of time, suggesting that these pathogenic oligomers are formed outside the nucleation-dependant fibril formation pathway (20).…”
supporting
confidence: 59%
“…This property has been recently demonstrated by Kayed et al (28), who reported that specific soluble oligomers called PFOs were able to seed their own replication upon interacting with monomeric A␤. The property of replication could be a manifestation of the unique structure of the oligomeric assembly and more importantly may complement our previously reported hypothesis that such oligomers are formed along a pathway different from fibril formation (1,19). To explore this, a 20 M sample of freshly purified, "seedfree" A␤42 was incubated with 0.4 M isolated LFAOs as seeds (2% molar ratio) at room temperature.…”
Section: Lfaos Are Replicating Strainsmentioning
confidence: 58%
“…The hyperbolic (concave) profiles exhibiting no inflection point or lag phase in the absence of seeding (Fig. 1a) are frequently reported in the literature during the aggregation of, for example, serum albumin (19,20), transthyretin (21,22), ␤ 2 -microglobulin (23), the four-repeat domain of Tau (24), apolipoprotein (25), and amyloid-␤ variants (26,27). This type of result is explained by the CLM as the result of predominant primary nucleation over the autocatalytic processes and is also well fitted by the "Ockham's razor" minimalistic model (18,28).…”
supporting
confidence: 58%
“…The anionic surface created by SDS has been found to promote fibril formation for a variety of proteins (33). In earlier studies by others, 0.2% SDS was reported to induce globular aggregates of Aβ; moreover, no fibrils were detected by atomic force microscopy (34).…”
Section: Discussionmentioning
confidence: 99%